Possible gas hydrates on the Bjarmeland Platform; seismic expression and stability modelling - Løvaas, John Sverre (UiT The Arctic University of Norway, 2016)
Seismic evidence of shallow gas anomalies are prominent at Ververis Dome structure and Hoop Fault Complex in Bjarmeland Platform. Ubiquitous high amplitude anomalies at the same depth as these shallow gas anomalies infer a possible relation to gas hydrates. A wide range of fluid flow structures within the two study areas have previously been discovered and reported, and may possibly feed the base of the gas hydrate stability zone (BGHSZ) with upward migrating thermogenic gas. This thesis focuses on seismic interpretation of gas hydrate-related bottom simulating reflectors (BSR) from high resolution 3D seismic data and high resolution 2D P-cable seismic data, as well as numerical modelling of gas hydrate stability conditions based on analyzed gas samples from geochemical data reports from well 7226/2-1 and 7324/8-1. Numerical modelling of present day gas hydrate stability conditions indicate favorable conditions for gas hydrate stability both in Ververis and Hoop Fault Complex. Furthermore, the estimated depth of gas hydrate stability from numerical modelling coincides with the interpreted BSRs in both study areas. As such, confidence is built in the interpretation and mapping of gas hydrates in the study areas. By using the results from ongoing work at Centre for arctic gas hydrate, environment and climate (CAGE) on numerical modelling of the ice sheet and isostatic conditions during the last glaciation, modelling of gas hydrate stability conditions indicate stable conditions for gas hydrates as deep as 618 m sub bottom depth in Ververis and 412 m sub bottom depth in Hoop Fault Complex during Last Glacial Maximum (LGM). The modelled gas hydrate stability zone in both study areas is thinning through deglaciation, possibly caused by unloading of vast ice sheets and the increasing bottom water temperatures.